Effect of Maternal Voice Recordings on Consciousness in Mechanically Ventilated Children in the PICU - Rahmadevita Septika; Fatmawati Fatmawati; Ema Julita; Rahmatika Ammelda; Rhahmadiani Fitri; Windu Reswari (GLOBAL HEALTH SCIENCE GROUP, 2026)
The Pediatric Intensive Care Unit (PICU) has limitations on family visitation, resulting in family-centered care not being optimally implemented. Meanwhile, pediatric patients who are mechanically ventilated in the PICU often experience decreased levels of consciousness due to sedation. One effort to maintain the emotional bond between mothers and their children and to improve the level of consciousness is through exposure to recorded maternal voices.This study aimed to evaluate the effect of maternal voice recordings on the level of consciousness of ventilated pediatric patients. This study used a quasi-experimental pretest–posttest design with a control group. A non-probability sampling technique with a consecutive sampling approach was applied. A total of 34 respondents were recruited, consisting of 17 participants in the intervention group and 17 in the control group. The intervention consisted of listening to maternal voice recordings, while the control group was exposed to non-maternal voice recordings. Data were collected through observation using the FOUR score. The data were analyzed using an independent t-test, and the results demonstrated that exposure to maternal voice recordings significantly improved the level of consciousness compared to non-maternal voice recordings. Maternal voice recordings can be considered a non-pharmacological intervention to enhance the level of consciousness in mechanically ventilated pediatric patients under sedation.